Hippocampal Transcriptome-Wide Association Study Reveals Correlations Between Impaired Glutamatergic Synapse Pathway and Age-Related Hearing Loss in BXD-Recombinant Inbred Mice - Deng, Tingzhi; Li, Jingjing; Liu, Jian; Xu, Fuyi; Liu, Xiaoya; Mi, Jia; Bergquist, Jonas; Wang, Helen; Yang, Chunhua; Lu, Lu; Song, Xicheng; Yao, Cuifang; et al. (Frontiers in Neuroscience, 2021)
Age Related Hearing Loss (ARHL) is associated with cognitive dysfunction, however the detailed mechanism remains unclear. The aim of this study is to investigate the potential underlying mechanism with a systems genetics approach. A transcriptome-wide association study was performed on aged (12-32 months) BXD mice strains. The hippocampus gene expression was obtained from 56 BXD strains, and the hearing acuity was assessed from 54 BXD strains. Further correlation analysis identified a total of 1435 hearing related genes in hippocampus (p < 0.05). Pathway analysis of these genes indicates that the impaired glutamatergic synapse pathway is involved in ARHL (p = 0.0038). The detailed molecular pathway analysis revealed altered glutamate receptor expression profiling, decreased glutamate synthesis, and enhanced cAMP signaling. More interestingly our gene co-expression analysis demonstrated that the expression level of glutamine synthetase (Gls), which is significantly correlated with ARHL(n = 26, r = -0.46, p = 0.0193), is a crucial regulator in glutamatergic synapse pathway, and associated with learning and memory behavior. In this study we present the first systematical evaluation of hippocampus gene expression pattern associated with ARHL, learning and memory behavior. This provides novel molecular mechanisms of association between ARHL and cognitive dysfunction.